[Ln16] complexes (Ln = GdIII, DyIII): molecular analogues of natural minerals such as hydrotalcite. Issue 37 (24th August 2018) - Richardson, Paul; Hsu, Ting-Jung; Kuo, Che-Jung; Holmberg, Rebecca J.; Gabidullin, Bulat; Rouzières, Mathieu; Clérac, Rodolphe; Murugesu, Muralee; Lin, Po-Heng
Abstract : Two new hexadecanuclear lanthanide complexes employing H2 bsc ligand are crystallized in the R 3̄ space group, which is unprecedented in a family of lanthanide complexes with such high nuclearity. Abstract : Two new hexadecanuclear lanthanide complexes employing the 1, 5-bis(salicylidene)carbohydrazide (H2 bsc) ligand are reported herein. These polynuclear aggregates crystallize in the R 3̄ space group, which is unprecedented in a family of lanthanide complexes with such high nuclearity. Magnetic susceptibility measurements reveal weak intramolecular interactions between the magnetic centres, and in the case of compound2 (Dy III ), single-molecule magnet properties are observed.